A FreeSurfer-compliant Consistent Manual Segmentation of Infant Brains Spanning the 0-2 year Age Range - Katyucia ede Macedo Rodrigues; Emma eBen-Avi; Danielle eSliva; Myong-sun eChoe; Marie eDrottar; Ruopeng eWang; Bruce eFischl; Patricia Ellen eGrant; Lilla eZöllei (Frontiers in Human Neuroscience, 2015)
We present a detailed description of a set of FreeSurfer compatible segmentation guidelines tailored to infant MRI scans, and a unique data set of manually segmented acquisitions, with subjects nearly evenly distributed between zero and two years of age. We believe that these segmentation guidelines and this dataset will have a wide range of potential uses in medicine and neuroscience.